In vitro Antioxidant, Acetylcholinesterase, and Amyloid-beta Inhibitory Effects of Captopril, An Angiotensin-Converting Enzyme (ACE) Inhibitor - Murugan, Raghul; Harshitha, Vantipalli Raga Sai; Parameswari, Royapuram Parthasarathy; Roy, Anitha (Biomedical Sciences and Clinical Medicine, 2026)
Objective This study aims to investigate the potential of captopril, an angiotensin-converting enzyme (ACE) inhibitor, to reduce reactive oxygen species (ROS) production and address critical factors associated with Alzheimer’s disease (AD) pathology, including acetylcholinesterase (AChE) activity and amyloid-beta (A ) peptide aggregation. The broader goal was to explore captopril’s neuroprotective properties and its potential as a therapeutic agent for AD. Methods The antioxidant effects of captopril were evaluated using DPPH and ABTS assays, as well as xanthine oxidase inhibition tests. The impact of captopril on AChE activity and A aggregation was assessed through in-vitro experiments. Molecular docking studies were conducted to analyze captopril’s binding affinity with essential AD-related proteins. Results Captopril demonstrated notable antioxidant activity with IC50 values of 71.99±0.40 µM (DPPH) and 106.3±0.28 µM (ABTS), comparable to ascorbic acid (92.32 ± 0.26 µM and 110.1±0.24 µM). Significant inhibition of xanthine oxidase activity was observed; however, the IC50 value exceeded the maximum tested concentration of 320 µM for both captopril and ascorbic acid. Captopril showed AChE inhibitory activity with an IC50 of 208.2 ± 0.36 µM, whereas donepezil exhibited an IC50 of 79.05 ± 0.25 µg/mL. In the A aggregation assay, captopril had an IC50 of 87.69±0.25 µM, while donepezil also displayed significant inhibition, with an IC50 above 320 µM. Molecular docking analyses revealed favourable binding interactions of captopril with AChE and A -related targets, supporting its multitarget mechanism. Conclusions Captopril demonstrated notable neuroprotective effects, including antioxidant activity and the inhibition of AChE activity and A aggregation. These findings indicate that captopril holds promise as a therapeutic agent for AD, warranting further research and clinical trials to evaluate its efficacy in combating neurodegeneration.